Rancang Bangun Sistem Informasi Monitoring Dan Evaluasi Pembangunan Sarana Dan Prasarana Pada Dinas Perhubungan Kota Surabaya - Priaditya, Nanda Cahya; Supriyanto, Antok; Maulana, Yoppy Mirza (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Transportation Department of Surabaya in particular the Deputy Transport Infrastructure which has activities that organize and establish management and control communications infrastructure. Problems faced could not be monitoring the progress of time and project work in the field. So the evaluation and early identification of problems that arise in the field so the prevention and settlement can not be immediately implemented and carried out repairs upcoming activities.To cope with the problem it was designed monitoring and evaluation information system penmbangunan facilities and infrastructure, the system is run by media websites that will be accessed easily through a smartphone, phablet, tablets and devices that can access other internet used by field supervisors.It was concluded that the application to assist and facilitate the task of the stakeholders in the process of monitoring and evaluation of development projects at the Department of Transportation in Surabaya. This is seen in the results of the implementation of the application of the results of this study. Keywords: Information Systems, Monitoring and Evaluation, Facility and infrastructure